1994
DOI: 10.1017/s0967199400001908
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-egg fusion in the sea urchin is blocked in Mg2+-free seawater

Abstract: SummaryMagnesium ions as well as calcium ions are required for successful fertilisation in sea urchins. In the absence of Mg2+ spermatozoa attached to the egg plasma membrane, their acrosomal processes passing through the vitelline envelope, but could not enter the egg cytoplasm (Sano et al, Dev. Growth Differ. 22, 531–41,1980). Such an individual spermatozoon was observed microscopically to resume entry into the egg immediately after the addition of a sufficient amount of Mg2+ to the surrounding medium. Neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Internalized sperm were detected according to the method of Mohri et al (1994). Oocytes or eggs, to which DNA staining fluorescent dye, mithramycin A (Sigma), had been injected to a final concentration of 100 µM, were inseminated at a 1000-fold dilution, 5 min later fixed with 1% glutaraldehyde (Wako Pure Chemicals, Oosaka, Japan) for 30 s, followed by washing with FSW, and observed under a BH-2 fluorescence microscope (Olympus).…”
Section: Detection Of Internalized Spermmentioning
confidence: 99%
“…Internalized sperm were detected according to the method of Mohri et al (1994). Oocytes or eggs, to which DNA staining fluorescent dye, mithramycin A (Sigma), had been injected to a final concentration of 100 µM, were inseminated at a 1000-fold dilution, 5 min later fixed with 1% glutaraldehyde (Wako Pure Chemicals, Oosaka, Japan) for 30 s, followed by washing with FSW, and observed under a BH-2 fluorescence microscope (Olympus).…”
Section: Detection Of Internalized Spermmentioning
confidence: 99%
“…It is difiBcult to precisely remove ASW by centrifiigation (Ciapa and Maggio, 1993) fi-om samples at 10 sec interval during the first 2 min of fertilization. Although sea urchin eggs can be fertilized in a Ca^^-fi-ee medium by using acrosome-reacted sperm (Schmidt et al, 1982), there is a requirement for in ASW during sea urchin fertilization (Sano and Mohri, 1976;Mohri et al, 1994). Preliminary trials showed a low and inconsistent fertilization rate using ASW with low amounts of Ca^ and Thereafter we determined a reduction of Ca^"^ and Mg^* contents in ASW in half was sufficient for high fertilization rate with minimal interference of the assay by chelating the residual and Mg^* with additions of 10 mM EGTA and 40 mM EDTA in 2 N KOH for neutralization of phosphoric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Eggs in a 1% egg suspension were mixed with an equal amount of Ca^^ and Mg^^-free ASW consisting of 545 mM NaCl, 11.4 mM KCl and 6 mM NaHCCb, pH 8 (Mohri et al, 1994), to make a 0.5% egg suspension in a solution with only half of the Ca^^ and Mg^" contents in normal ASW (l/2CaMgASW). Eggs were then incubated with or without 20 jiM U73122 in a 0.5% egg suspension for 5 min and reconstituted to 7.5% before insemination.…”
Section: Inspj Mass Assaymentioning
confidence: 99%